Modified zeolite in a sustainable, circular economy-based process for enhanced ammonium recovery from wastewater - Dipshika Das; Sukalyan Sengupta (Cleaner Water)
Ammonia is vital for sustaining global food production, but its synthesis via the Haber-Bosch process comes with a significant energy demand. Additionally, a large portion of produced ammonia is discharged into wastewater, where conventional treatment methods convert it to nitrogen gas through energy-intensive processes that also carry the risk of greenhouse gas emissions. Developing technologies that directly recover ammonia from wastewater and recycle it as fertilizer offers substantial social, environmental, and economic benefits, in line with the principles of a circular economy. This study introduces Hydrothermal + Alkali Treated Chabazite (HATCH), a natural zeolite modified to function as a highly efficient ion exchanger for ammonium removal. Detailed analyses reveal that HATCH’s ammonium uptake surpasses conventional ionexchange principles due to two key factors: (i) the presence of Brønsted acid sites and (ii) the exclusion of hydrated cations from the HATCH framework caused by their ionic radii. In a fixed-bed column configuration, HATCH selectively removes ammonium from wastewater and can be regenerated using brine, producing an ammonium-rich solution. This solution can be further processed into solid or liquid ammoniacal fertilizers. HATCH exhibits strong durability, maintaining its efficiency across multiple exhaustion-regeneration cycles.